UTILIZATION OF MARBLE SLURRY TO ENHANCE SOIL FERTILITY AND TO PROTECT ENVIRONMENT - PRERNA SUDAN,; RITU MATHUR,; M.P.S. CHANDRAWAT,; SWATI JAIN, (International Journal of Pharma and Bio Sciences, 2015)
Rajasthan is a rocky state having oldest Aravali ranges, which are very rich in diverse minerals, particularly dolomite, granite and marble. Hence, so many industries in Rajasthan are based on these rocks. However, during mechanical processing of these minerals, about 30%-40% part is left as a waste in the form of slurry. These mineral wastes could be used as a source of macro and micronutrients for soil. XRF analysis was done to evaluate the composition of marble slurry. Result of XRF revealed that 30.52% of calcium, 9.95% of magnesium, 1.57% of iron, 0.05% of potassium, 0.09% of phosphorous and 0.07% of manganese present in it. XRF analysis of marble waste also showed the presence of ultra micro nutrients and REEs (Rare Earth Elements). It is found to be an effective combination to provide macro and micro nutrients for soil.